Merancang Aplikasi Penjualan Piko Bakery Berbasis Windows - Putri Wulandari; Rizky Basatha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the rapidly evolving era of digitalization, the need to enhance operational efficiency in the business sector has become increasingly urgent, including for businesses such as Piko Bakery. Piko Bakery is a bakery that produces various types of bread, such as sweet bread, plain bread, jam-filled bread, and roti buaya. Over the past six months, operations have still been conducted conventionally, particularly in managing the procurement of raw materials, bread sales, and administrative recording. This has led to several challenges, including difficulties in monitoring inventory levels, the absence of adequate sales recapitulation, and a lack of accurate financial and revenue transaction reports. To address these issues, the PIKO Bakery application was developed to facilitate sales management, product inventory tracking, and real-time transaction monitoring. This application offers essential features such as sales transaction recording, real-time inventory management, and the generation of financial and inventory reports. Implementation results show that using the PIKO Bakery application accelerates transaction processes, reduces errors in inventory management, and simplifies sales report preparation. Therefore, this system is expected to automate business processes, improve data accuracy, and support better decision-making for business owners.